1965
DOI: 10.1149/1.2423332
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of Silicon in Gallium Phosphide

Abstract: Gallium phosphide was prepared using a horizontal refining technique. The liquid zone was maintained close to the stoichiometric composition. An ingot, doped with silicon, was zone refined. From electrical, optical transmission, and spectrochemical measurements, it is demonstrated that silicon (at concentrations in the range of 1018 at./cc) is a donor impurity with an activation energy of 0.06 ev, that silicon substitutes for gallium, and that the segregation coefficient for silicon in normalGaP is 0.6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1967
1967
1972
1972

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Low temperature Hall measurements and more recent cathodoluminescent studies haveindicated silicon 170 to be the predominant background impurity with small amounts of sulphur also present. This corresponds to observations reported previously [10,11 ] which showed that with similar apparatus and techniques to those described in this paper the total atomic Si content (k0 ~ 0.6) would be approximately 5 x 1017 cm -~ for layers grown on (I 1 1) substrates. The value of ND --NA calculated from the capacitance data is plotted in fig.…”
Section: Resultssupporting
confidence: 92%
“…Low temperature Hall measurements and more recent cathodoluminescent studies haveindicated silicon 170 to be the predominant background impurity with small amounts of sulphur also present. This corresponds to observations reported previously [10,11 ] which showed that with similar apparatus and techniques to those described in this paper the total atomic Si content (k0 ~ 0.6) would be approximately 5 x 1017 cm -~ for layers grown on (I 1 1) substrates. The value of ND --NA calculated from the capacitance data is plotted in fig.…”
Section: Resultssupporting
confidence: 92%
“…The main impurity detected, silicon, does not seem to play the role generally allocated to it. Previous results (11,12) report it to be a net shallow donor. At least at concentrations below 1017/cm3 this is in disagreement with the present data.…”
Section: Resultsmentioning
confidence: 81%